Faros y pantanos. Una historia de las prisiones provinciales argentinas (Córdoba, Santa Fe y Tucumán, 1853-1946) - González Alvo, Luis (Historia del Derecho, 2022)
Beacons and swamps is a proposal for dialogue with the historiography of Argentine prisons, which saw provincial prisons as "swamps": immobile, grey, unchanging spaces. Although it is true that the pace of change in the provinces differed enormously from that of the capital, the work of the local prison reformers was to build "beacons" of modernity, in the style of the one installed in Buenos Aires: the famous National Penitentiary. Much has been discussed about the "panopticon", that institutional model of the society of control, but little is known about those "swamps" that constituted "the grey punishment of the majority". The aim of this book is to explore what is hidden in those provincial confinement spaces, where most of the national prison population was punished. It is based on the hypothesis that it is precisely there, under those swamps, that the original Argentine prison is hidden, because it was forged in those grey places of transition rather than in the "modernising beacons" of Buenos Aires or Ushuaia. Far from the "model", and from the punitive "should be", the embryos of the contemporary prison are hidden in the marshes. Delving into the mud and unearthing these vestiges, investigating the logic of the functioning of provincial prisons, will allow a better understanding of the emergence and consolidation of the punitive devices that characterise Argentine prisons today.